Simultaneous Improvement of Dissolution Behavior and Oral Bioavailability of Antifungal Miconazole via Cocrystal and Salt Formation - Ksenia V. Drozd; Alex N. Manin; Denis E. Boycov; German L. Perlovich (MDPI AG, 2022)
Miconazole shows low oral bioavailability in humans due to poor aqueous solubility, although it has demonstrated various pharmacological activities such as antifungal, anti-tubercular and anti-tumor effects. Cocrystal/salt formation is one of the effective methods for solving this problem. In this study, different methods (liquid-assisted grinding, slurrying and lyophilization) were used to investigate their impact on the formation of the miconazole multicomponent crystals with succinic, maleic and dl-tartaric acids. The solid state of the prepared powder was characterized by differential scanning calorimetry, powder X-ray diffraction and scanning electron microscopy. It was found that lyophilization not only promotes partial amorphization of both salts but also allows obtaining a new polymorph of the miconazole salt with dl-tartaric acid. The lyophilized salts compared with the same samples prepared by two other methods showed better dissolution rates but low stability during the studies due to rapid recrystallization. Overall, it was determined that the preparation method of multicomponent crystals affects the solid-state characteristics and miconazole physicochemical properties significantly. The in vivo studies revealed that the miconazole multicomponent crystals indicated the higher peak blood concentration and area under the curve from 0 to 32 h values 2.4-, 2.9- and 4.6-fold higher than the pure drug. Therefore, this study demonstrated that multicomponent crystals are promising formulations for enhancing the oral bioavailability of poorly soluble compounds.